O homem idoso e o contexto da institucionalização - Riffel, Rogerio Tomasi (2018)
The elderly man becomes a new actor within the context of institutionalization, facing the demands of care, because, today with the evolution of the treatments and the emergence of new technologies in the area of health, this population segment began to experience the phenomenon of longevity . This study aimed to know the look with which the elderly man perceives this context of institutionalization, delineated a qualitative, exploratory and descriptive research. Elderly men living in long-term care institutions for the elderly in the municipality of Passo Fundo - RS participated. Data were collected through semi-structured interviews, guided by guiding questions that included the point of view about living in the institution, their expectations and feelings experienced from institutionalization, the same occurred in the period from March to April 2018. content analysis, more specifically, thematic analysis technique, which allowed grouping into four categories: the decision-making process; the reasons for institutionalization; on links and disruptions; and the unveiling of finitude: between mourning and illusory. It was concluded about institutionalization, it follow principles common to decisions generally meets the interests of a certain party. Decision making, usually part of the family, cognitive and functional decline, are the main reasons for institutionalization. The affective bond that endures in spite of distance and disease; as well as autonomy and vitality, allow it to maintain a more harmonious relationship with the institutionalization process. Being this a process of mourning, the use of healthier psychic mechanisms and hope, help a lot in this phase of life.